Wave propagation behaviour of functionally graded material plates based on neutral surface position - BOUKHARI, Ahmed; BOURADA, Fouad; BAKORA, Ahmed; BOURADA, Mohamed; TOUNSI, Abdelouahed (University of Eloued جامعة الوادي, 2018)
In this paper, an efficient higher-order shear deformation is developed for dynamic analysis of plate in the presence of thermal environments. By dividing the transverse displacement into bending and shear parts, the number of unknowns and governing equations of the present theory is reduced, The thermal effects and temperature-dependent material properties are both taken into account. The temperature field is assumed to be a uniform distribution over the plate surface and varied in the thickness direction only. Material properties are assumed to be temperature-dependent, and graded in the thickness direction according to a simple power law distribution in terms of the volume fractions of the constituent’s isotropic plates. It can be concluded that the present theory is not only accurate but also simple in predicting the wave propagation characteristics in the functionally graded plate
International Symposium on Mechatronics and Renewable Energies El-Oued 10- 11 December 2018
Keywords: Wave propagation, P-FGM plate, Thermal effects, Higher order theory, Neutral surface position